May-June 2023 California Current Thermosalinograph Data - Yayla Sezginer; Adrian Marchetti; Claire Till (PANGAEA, 2025)
Oceanographic properties were measured during the Phytoplankton UPwelling response CYCLE (PUPCYCLE) II expedition May 27-June 12, 2023 during a transit between Newport, OR and San Francisco, CA onboard the R/V Sally Ride. Temperature and salinity were measured with a SBE 45 MicroTSG connected to ship extquotesingles seawater supply line (~5m nominal depth). Chlorophyll and Oxygen concentrations were measured with a Seabird Chlorophyll Fluorometer and an oxygen optode, respectively.